Improvement of phase sensitivity in SU(1,1) interferometer using number-conserving operations - Jie Tang; JiaHao Li; YueXiang Cao; Ying Liu; HaoRan Hu; Ya Wang; Dan Wu; ZhiFeng Deng; HuiCun Yu; XingYu Wang; HuaZhi Lun; JiaHua Wei; et al. (Results in Physics, 2024)
We propose a theoretical scheme to improve the phase sensitivity by introducing the number-conserving generalized superposition of product into squeezed thermal state of the traditional SU(1,1) interferometer with intensity detection. We investigate the effect of different parameter and photon losses on phase sensitivity under the condition of the ideal and the realistic phase estimation process, respectively. Moreover, compared with the previous methods, our scheme can not only enhance the phase sensitivity, but also significantly suppress the photon losses with only first-order GSP operation. It means that our scheme needs less resources and less operations to obtain higher phase sensitivity. These above results indicate that our scheme is viable in the phase sensitivity improvement, which may have practical applications in quantum information processing.